Analisis Break Even Point Sebagai Alat Perencanaan Penjualan Pada Perusahaan Rokok Sidomulyo Sidoarjo - Toto Heru Dwihandoko; Rini Armin; M. Adik Rudiyanto; Muhamad Rifa’i (Program Studi Manajemen, Fakultas Ekonomi, Universitas Islam Majapahit, Jawa Timur, Indonesia, 2022)
Budgeting or budgeting is a process of planning and controlling the company's operations which are expressed in units of activity and units of money which aim to project the company's operations in the projected financial statements. Production activities are one of the functions in company activities that require management planning and control, because the process involves various resources that must be used efficiently, so that control over these activities determines the success or failure of a company in achieving its objectives.